Medication errors in pediatrics: Evaluation of spontaneous reports in a pediatric hospital in Porto Alegre, RS, Brazil: DOI: 10.15343/0104-7809.202044068075 - Zanella Lazaretto, Francieli (2020)
This study aimed to quantify medication errors spontaneously reported by professionals working in a pediatric hospital. Thiswas a quantitative and retrospective study carried out in a philanthropic, teaching pediatric hospital, with a total of 184 beds,of which 144 are inpatient beds and 40 are ICU beds. Adverse event data recorded on a form available on the institutionalintranet from January 1, 2015 to December 31, 2018 were collected. 471 events related to medication errors were recorded.The incorrect dose with the highest number of notifications in the years 2016, 2017 and 2018 (22.4%, 26.2% and 24%consecutively) stood out. In 2015 the largest number of notified events was related to the omission of dose or medication(20.8%). Dose errors were grouped into three distinct subclasses: overdose, underdose and extra dose. Doses higher thanrecommended are highlighted in all evaluated years, with rates above 70% of notifications. Highly supervised drugs,antimicrobials, controlled drugs and chemotherapy were the most frequently reported. The quantification of medicationerrors reported in pediatrics was essential to know their profile and focus on actions to improve processes. Educationalactions motivating the registration of notifications by all professionals are essential to strengthen the culture of patient safety.